Electrospun Fibers in Composite Materials for Medical Applications - Baptista, A.C.; Ferreira, I.; Borges, J.P. (Journal of Composites and Biodegradable Polymers, 2013)
The development of nanoscaled materials has deserved a remarkable interest for biomedical applications. Biological tissues are essentially composite materials with particular mechanical properties that should be carefully considered during the design of innovative biomedical scaffolds. Electrospun membranes are often found in medical applications due to its high specific surface which creates a 3D porous structure that mimics the native extracellular matrix. These electrospun membranes can also be designed to have enhanced mechanical properties, biocompatibility and cellular response making them appealing and inspiring to be used in composites materials. This paper reviews the new insights in the development of advanced nanostructured composites materials based on electrospun fibers. From tissue engineering to bioelectronics, these composite materials can be found in the most promising research developments for the medical applications.